2010
DOI: 10.1007/s11908-009-0075-6
|View full text |Cite
|
Sign up to set email alerts
|

Non–AIDS-Defining Malignancies in Patients with HIV in the HAART Era

Abstract: The introduction of highly active antiretroviral therapy (HAART) has drastically changed the scope and spectrum of diseases associated with HIV, shifting from AIDS-related to non-AIDS-related diseases. Studies linking HIV/AIDS databases to cancer registries have shown a dramatic decrease in AIDS-related malignancies and a steady increase in non-AIDS-defining malignancies (NADM). We review the causes underlying the rise in incidence of NADM and the clinical presentation, pathology, and treatment outcomes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 52 publications
1
30
0
2
Order By: Relevance
“…A correlation between the effectiveness of immune reconstitution following antiretroviral treatment, measured as CD4 ϩ T-lymphocyte counts, and the bifunctionality of total NK cells demonstrated that more effective control of HIV disease was associated with higher NK cell functionality. However, the lack of correlation between treatment efficacy and the NK cell education ratio is interesting, as it may provide a partial explanation for the higher incidence of non-AIDS-defining malignancies (NADMs) in HAART-treated HIV-infected individuals than in the general population (24). Future studies using larger sample sizes and following subjects over time will help elucidate the factors determining why some HIV-infected individuals exhibit normal NK cell education ratios and the potential role of these ratios in susceptibility to NADMs.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between the effectiveness of immune reconstitution following antiretroviral treatment, measured as CD4 ϩ T-lymphocyte counts, and the bifunctionality of total NK cells demonstrated that more effective control of HIV disease was associated with higher NK cell functionality. However, the lack of correlation between treatment efficacy and the NK cell education ratio is interesting, as it may provide a partial explanation for the higher incidence of non-AIDS-defining malignancies (NADMs) in HAART-treated HIV-infected individuals than in the general population (24). Future studies using larger sample sizes and following subjects over time will help elucidate the factors determining why some HIV-infected individuals exhibit normal NK cell education ratios and the potential role of these ratios in susceptibility to NADMs.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the incident of non-AIDSdefining-malignancy (NADM) has increased. Unfortunately, in these patients, such malignancies present at an earlier age and usually follow a more aggressive course (8,9). The exact reasons for this observation are unknown; however, many experts hypothesize that it may be partly due to the profound immune disarrangement produced by the HIV virus in their hosts (10).…”
Section: Introductionmentioning
confidence: 99%
“…This means that HIV-positive individuals live long enough to experience cancers that are more common in older individuals. A substantial amount of research is now being conducted on non-AIDS-defining malignancies in patients with HIV in the post-HAART era (Grulich et al, 2007;Nguyen et al, 2010;Shiels et al, 2011). The number of cancer sites wherein incidence is higher in HIV-positive individuals includes Hodgkin lymphoma, melanoma, leukaemia, and cancers of the liver, lung, anus, vagina, oropharynx, colon or rectum, and kidney.…”
Section: Human Immunodeficiency Virus and Cancersmentioning
confidence: 99%